Register Mobile Ads on Olx Online Sale and Purchase Sites: Sociolinguistic Studies - Rizqi Hidayatulloh; Tri Pujiati (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Advertisements in online trading sites OLX is a communication process that certainly varies in shape. This study aims to (1) describe the form of registers, (3) describe the meaning of registers, and (3) describe the language functions in the registers contained in advertisements of mobile phone in online trading sites OLX. This study uses descriptive qualitative method with Sociolinguistics perspective. Data are taken from OLX advertisement by using sampling method which then captured the screen data for further categorization and analysis. The results of the study are that (1) the form of registers contained in advertisements of mobile phone on the OLX online trading site contains a single form and complex form of affixation, abreviation and repetition; (2) the meaning of register on mobile phone at OLX online trading site is in the form of lexical, grammatical meaning, and contextual meaning; and (3) language functions in OLX online buying and selling of mobile phone registers are instrumental functions, regulatory functions, representation functions, interactional functions, and personal functions. Abstrak Iklan dalam situs jual beli online OLX merupakan sebuah proses komunikasi yang tentu bervariasi bentuknya. Penelitian ini bertujuan untuk (1) mendeskripsikan bentuk register, (2) mendeskripsikan makna register, dan (3) mendeskripsikan fungsi bahasa pada register yang terdapat pada iklan ponsel dalam situs jual beli online OLX. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan sosiolinguistik. Data diambil dari iklan OLX yang dikumpulkan dengan menggunakan metode sampling yang kemudian data di tangkap layar untuk selanjutnya di kategorikan dan di analisis. Hasil penelitian ini menunjukkan bahwa (1) bentuk register yang terdapat dalam iklan ponsel pada situs jual beli onlie OLX yaitu bentuk tunggal dan bentuk kompleks berupa afiksasi, abreviasi dan pengulangan; (2) makna register iklan ponsel pada situs jual beli online OLX berupa makna leksikal, gramatikal, dan makna konteekstual; dan fungsi bahasa pada register jual beli online OLX berupa fungsi instrumental, fungsi regulasi, fungsi representasi, fungsi interaksional, dan fungsi personal. Kata kunci : sosiolinguistik, ragam bahasa dan register